Impact of Body Composition and Physical Function on Quality of Life After Gastrectomy for Gastric Cancer - Wang, Wen-Bin; Song, Hao-Nan; Huang, Dong-Dong; Luo, Xin; Cai, Hui-Yang; Yan, Jing-Yi; Chen, Wei-Zhe; Xing, Chun-Gen; Dong, Qian-Tong; Chen, Xiao-Lei (Frontiers in Surgery, 2022)
Purpose: Patients with gastric cancer after gastrectomy often suffer from a decline in their quality of life (QoL), but the relationship between body composition (BC) and physical function on QoL has rarely been studied. This study aims to evaluate and determine the changes in QoL after gastrectomy and the relationship between BC and physical function on QoL. Methods: A total of 311 gastric cancer patients completed EORTC QLQ-C30 and EORTC QLQ-STO22 questionnaires prior to and 1, 3, 6 months post-surgery. Data including BC, handgrip strength (HGS) and 6-meter gait speed (GS) are collected prospectively. Multiple linear regression determined the correlation between preoperative and postoperative QoL and BC, HGS and GS. Results: Gastrectomy patients had significantly worse scores on most function and symptom scales (p <0.001), but most functions and symptoms recovered within 6 months after surgery. A higher subcutaneous fat area（SFA）was associated with increased symptom scores1 month post-surgery. A higher GS is associated with a better global health status and decreased symptom score. Conclusion: Patients after gastrectomy suffer from a decline in their QoL. Intervention strategies aimed at reducing SFA and improving GS may improve the QoL of gastric cancer patients.